IgG4 drives M2a macrophages to a regulatory M2b‐like phenotype: potential implication in immune tolerance. Issue 3 (28th November 2018) - Bianchini, Rodolfo; Roth‐Walter, Franziska; Ohradanova‐Repic, Anna; Flicker, Sabine; Hufnagl, Karin; Fischer, Michael Bernhard; Stockinger, Hannes; Jensen‐Jarolim, Erika
Abstract: Background: Macrophages can be converted in vitro into immunoregulatory M2b macrophages in the presence of immune complexes (ICs), but the role of the specific subclasses IgG1 or IgG4 in this phenotypic and functional change is not known. Objective: We aimed to refine the original method by applying precisely defined ICs of the subclasses IgG4 or IgG1 constructed by two independent methods. Methods: Monocyte‐derived macrophages (MDMs) were treated with M‐CSF, followed by IL‐4/IL‐13 to induce the M2a allergic phenotype. To mimic unspecific or allergen‐specific ICs, plates were coated with myeloma IgG1 or IgG4, or with grass pollen allergen Phl p 5 followed by recombinant human Phl p 5‐specific IgG1 or IgG4. M2a polarized macrophages were then added, cultured, and examined for cellular markers and cytokines by flow cytometry, ELISA, and rtPCR. Alternatively, immune complexes with IgG1 or IgG4 were formed using protein L. Results: IgG4 ICs down regulated CD163 and CD206 on M2a cells, and significantly increased IL‐10, IL‐6, TNFα, and CCL1 secretion, indicating a shift to an M2b‐like phenotype. Treatment with IgG4 ICs resulted in expression of FcγRII and down modulation of FcγRII compared with IgG1 treated cells ( P  = 0.0335) or untreated cells ( P  < 0.00001). Conclusion: Immune complexes with subclasses IgG1 and IgG4 can in vitro be generated by plate absorption, and in fluid form by protein L. Cross‐linking of FcγRIIb by the IgG4 subclass redirects pro‐allergic M2a macrophages to an M2b‐like immunosuppressive phenotype. This suggests an interplay of macrophages with IgG4 in immune tolerance, likely relevant in allergen immunotherapy. Abstract : This study highlights the central role of IgG4 in immune tolerance. The treatment of M2a with ICs consisting of IgG4 shows a considerably greater effect in promoting an M2b‐like phenotype than with IgG1‐containing ICs. The secretion of CCL1 and IL‐10 by M2b‐like macrophages is important to establish a tolerogenic microenvironment.